Wiara kształtowana przez Objawienie. Refleksja nad wiarą jako „adekwatną odpowiedzią” - Małyga, Maciej (Poznańskie Studia Teologiczne, 2020)
Faith is not man’s own project, but his adequate response to Revelation, the personal self-giving of God in history. Because the initiative of Revelation is an absolute condition for the possibility of faith, it gives faith a concrete shape — the specific features of Revelation shape the way faith is formed. The first feature of Revelation is the fact that the Word of God spoke in the human word, that is why faith is not a direct view of the Divine, but it is carried out by reception of what is immanent. The next feature of Revelation is the dialectic of the self-revealing and self-veiling of God. Faith in a natural way is thus stirred with questions, it cannot be manipulated and possessed. The third feature of Revelation, the one that most affects the specific shape of faith, is the fact that it was ultimately accomplished by the Divine Person of the Logos who accepted human nature. Historically becoming the person of Jesus Christ, who is the “universale concretum”, and living in a specific time and space, he embodies in himself the ultimate saving will of God for every human being. The bond with the saving God is accomplished through a bond with Jesus Christ, present today in his Body, which is the Church.